Accelerated transformation: designing global online higher education. Issue 7 (9th November 2020) - Guo, Fei; Hong, Xi; Coates, Hamish
ABSTRACT: Studying higher education in 2020 has confirmed the difficulty of foresight analysis and need for courageous redesign of education fundamentals. This paper discusses the shift made by Tsinghua University into full online provision and considers broader implications for higher education. It articulates the emergence of global online higher education, and the capabilities underpinning this transformation. Drawing from the study of contemporary developments in China and the world, the paper concludes that now is the time for bold education experiments, informed by major useful university design.